2003
DOI: 10.1096/fj.02-0586fje
|View full text |Cite
|
Sign up to set email alerts
|

The antimycotic ciclopirox olamine induces HIF‐1α stability, VEGF expression, and angiogenesis

Abstract: The heterodimeric hypoxia-inducible factor (HIF)-1 is a master regulator of oxygen homeostasis. Protein stability and transactivation function of the alpha subunit are controlled by iron- and oxygen-dependent hydroxylation of proline and asparagine residues. The anti-mycotic ciclopirox olamine (CPX) is a lipophilic bidentate iron chelator that stabilizes HIF-1alpha under normoxic conditions at lower concentrations than other iron chelators, probably by inhibiting HIF-1alpha hydroxylation. As shown by the inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
82
1
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(89 citation statements)
references
References 56 publications
5
82
1
1
Order By: Relevance
“…It is most useful against tinea versicolor (Niewerth et al, 2003). Antimycotic ciclopirox olamine also acts as a bidentate iron chelator capable of stabilizing HIF-1α and then activating endogenous HIF-1 target genes, including VEGF to promote angiogenesis remodeling (Linden et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…It is most useful against tinea versicolor (Niewerth et al, 2003). Antimycotic ciclopirox olamine also acts as a bidentate iron chelator capable of stabilizing HIF-1α and then activating endogenous HIF-1 target genes, including VEGF to promote angiogenesis remodeling (Linden et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However, none of the previously studied iron chelators (desferrioxamine, desferri-exochelin, ciclopirox olamine, 2,2′-dipyridyl, and dibenzoylmethane) that activate HIF-1 under normoxic conditions inhibit hypoxic activation of HIF-1. 19,[21][22][23] Compound 1 (ECG) appears to play dual opposing roles that differentially regulate HIF-1 activity, depending on the concentration of oxygen in the cellular environment. While screening small molecule natural products for HIF-1 inhibitors, we observed that certain green tea catechins activate HIF-1 under normoxic conditions in a T47D human breast tumor cell-based reporter assay.…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that these sequences are necessary, but not sufficient for HIF-1 mediated transcription as surrounding nucleotides are also important. Several HIF-1-dependent reporter systems, that used the HREcontaining portions of promoters/enhancers or multimerized HIF-1 binding sites, were previously described (Forsythe et al, 1996;Shibata et al, 1998Shibata et al, , 2000Koshikawa et al, 2000;Post and Van Meir, 2001;Rapisarda et al, 2002;Su et al, 2002;Burroughs et al, 2003;Hanze et al, 2003;Linden et al, 2003). However it was noticed that a large portion of upstream region from HIF-1-responsive gene can be responsible for HIF-1-independent activation of a reporter gene expression (Burroughs et al, 2003).…”
Section: Discussionmentioning
confidence: 99%